Current bioinformatics tools for biodegradation of xenobiotic compounds - Arora, Pankaj Kumar; Kumar, Ashish; Srivastava, Alok; Garg, Sanjay Kumar; Singh, Vijay Pal (Frontiers in Environmental Science, 2022)
The review summarizes different bioinformatics tools used in studying the degradation of various xenobiotic compounds. Databases and Pathway Prediction Systems are the key bioinformatics tools involved in biodegradation. Several bio-degradative databases including EAWAG-BBD (Biocatalysis/Biodegradation Database), Plastics Microbial Biodegradation Database, ONDB (Organonitrogen Degradation Database), Food risk component database (Food risk component database, Aromadeg (Aromatic hydrocarbon Degrading Database), OxDBase (A database of Biodegradative oxygenases), and RHObase database (ring-hydroxylating oxygenase database) have been developed for biodegradation and bioremediation studies. Users can use pathway prediction systems to predict degradation of xenobiotic whose degradation has never been reported in the literature. This review will help to design a strategy for biodegradation of chemicals therefore, also help in improved bioremediation process of chemicals.